ANALISIS PARTISIPASI KOMUNITAS LOKAL DALAM PENGEMBANGAN DAYA TARIK WISATA KOTA TUA JAKARTA - Waranei Muntu, Adrianus; Suryawan Wiranatha, Agung; Sukma Arida, I Nyoman (Jurnal Master Pariwisata (JUMPA), 2018)
This article analyzed the participation of the local communities to develop the tourist attractions in the Old Town of Jakarta which was conducted to determine the forms of participation necessary for the local communities, to determine the factors which a ect the participation, and the impact of their participation. The methods utilized in this article are qualitative methods with data collection through interviews, observation, literature review, and document analysis. This article explains the forms of participation of the local communities which involve creating and showing new tourist attractions and preserving the existing tourist attractions. The factors which a ect the participation are divided into two types: supporting factors and the obstacles. In addition, this article also managed to nd the impact of the local communities participation which divided into two types: positive and negative impacts. The expected result of this article is to contribute to developing the tourist attractions and sustainable tourism in Jakarta as well as Jakarta’s Old Town in particular.